Role of the RAM Network in Cell Polarity and Hyphal Morphogenesis in Candida albicans - Song, Yunkyoung (The American Society for Cell Biology, 2008)
RAM (regulation of Ace2p transcription factor and polarized morphogenesis) is a conserved signaling network that regulates polarized morphogenesis in yeast, worms, flies, and humans. To investigate the role of the RAM network in cell polarity and hyphal morphogenesis of Candida albicans, each of the C. albicans RAM genes (CaCBK1, CaMOB2, CaKIC1, CaPAG1, CaHYM1, and CaSOG2) was deleted. All C. albicans RAM mutants exhibited hypersensitivity to cell-wall- or membrane-perturbing agents, exhibiting cell-separation defects, a multinucleate phenotype and loss of cell polarity. Yeast two-hybrid and in vivo functional analyses of CaCbk1p and its activator, CaMob2p, the key factors in the RAM network, demonstrated that the direct interaction between the SMA domain of CaCbk1p and the Mob1/phocein domain of CaMob2p was necessary for hyphal growth of C. albicans. Genome-wide transcription profiling of a Camob2 mutant suggested that the RAM network played a role in serum- and antifungal azoles–induced activation of ergosterol biosynthesis genes, especially those involved in the late steps of ergosterol biosynthesis, and might be associated, at least indirectly, with the Tup1p-Nrg1p pathway. Collectively, these results demonstrate that the RAM network is critically required for hyphal growth as well as normal vegetative growth in C. albicans.